International Financial Reporting Standard Adoption: How Does It Happened? - Roekhudin Roekhudin (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to investigate the determinants of the state’s voluntary adoption of international financial reporting standards (IFRS). The sample consisted of 120 countries that have adopted IFRS voluntarily based on the data released by IAS plus in 2019. The rate of IFRS adoption is measured using an interval scale based Deloyd’s criteria. The independent variables included economic growth, level of openness, education level, legal system, political factor and cultural factor with the corruption control as the moderating variable. The multinominal logistic regression test shows that all independent variables can determine the level of the state’s voluntary adoption of IFRS and the level of corruption control can moderate the relationship. The results of this study provide additional contributions to the literature evidence related to studies of IFRS voluntary adoption. In addition, this study is also able to accommodate a variety of complex factors with various economic, social, cultural and legal perspectives at the level of Jurisdictions.